Photoelectric Pattern of Afterpulses Generation in Avalanche Photodetectors - A. O. Zenevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The pattern of afterpulses generation in avalanche photodetectors, operating in the photon counting mode is offered. This pattern allows to take into account the trapped level type of carrier trapping, type of charge carrier, trapped on such level and the dead time effect.